Caminhos da memória no romance A Fortaleza dos Vencidos - Alves, Rosemary da Silva (2016)
The present research analyzes Nei Leandro de Castro's novel A Fortaleza dos Vencidos (2009) in order to investigate the construction of memory in the narrative as a recurrence of witness literature since the novel brings up social and political context of the period of the Military dictatorship. It is about observing, specifically, the memory inscribed in the literary work and how the voice that builds this memory brings up a literary representation of the history lived in that context, that, before the process of imposed forgetfulness, comes up to revive the memory of the reader and to revisit the social history of the country in a critical way. In the narrative of Nei Leandro de Castro, the characters are represented by ordinary people who suffered the tortures in the Years of Lead (Período de Chumbo), and, from a series of connected actions, they speak of the memories of their past; It is this aspect that this work is about. It is necessary to emphasize that the present work encompasses primarily the social and historical context in which the work is inserted, promoting dialogues between both, in order to perceive the way in which, in the author’s fiction, the articulation between the novel and the history, the literature and the social life. In order to discuss and establish relations between the literary text and historical reality, we sought theoretical support in the study of Daniel Aarão Reis though his book Ditadura e Democracia no Brazil (2014) as well as in Sérgio Luiz Bezerra Trindade through his researches on the history of Rio Grande do Norte. Regading the discussion about the memory inserted in this analysis, we have the contribution of Écléa Bosi (2009), Márcio Seligmann-Silva (2003) and Brandão (2008), as well as the theoretical contribution of Philippe Lejeune (2008) and Jacques Le Goff 1990). The research found that the studied novel, articulated with the social history of the country, more specifically with the context of the Military Dictatorship, portrays autobiographical features of Nei Leandro de Castro as well as the memorialistic side of the literary work through resignification of the author's memories related to that period.